Secret sins : sex, violence and society in Carmarthenshire, 1870-1920 - Davies, Russell, 1957- (University of Wales Press, 2012)
Sleepy rustic Carmarthenshire was secretly a hotbed of debauchery, violence and drunkenness according to Russell Davies in a new edition of his very successful book, 'Secret Sins'. Behind the facade of idyllic rural life, there was a twilight world of mental illness, suicide, crime, vicious assaults, infanticide, cruelty and other assorted acts of depravity. This almost anecdotal historical study is often funny, sometimes disturbing, always revealing.